Advertising and Coordination - Kyle Bagwell; Garey Ramey (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1990)
We show that when relevant market information such as price is difficult to communicate, advertising plays a key role in bringing about optimal coordination of purchase behavior: an efficient firm uses advertising expenditures in place of price to inform sophisticated consumers that it offers a better deal. This provides a theoretical explanation for Benham's (1972) empirical association of the ability to advertise with lower prices and larger scale. We find that advertising improves welfare unambiguously when firms' price choices are the only source of uncertainty. When advertising must also signal the identity of the efficient firm, however, a welfare tradeoff arises between advertising and coordination. Our results extend readily to situations of partial price observability and product quality uncertainty.
Keywords: 330